Forest in systemic perspective: Weaknesses and strengths - Embros, Grzegorz (Studia Ecologiae et Bioethicae, 2018)
In this paper, some exemplary methods of describing both a ‘forest’ system and its subsystems are presented. In order to precisely offer the manner of constructing a systemic image of the forest and its subsystems, all issues related to the systemic approach are clarified. The weaknesses and strengths of such an approach were juxtaposed and revealed the possibilities of using them to shape the man–forest relationship. Attention was paid to the ‘expanding of interpretation’ of the systemic approach and the subsequent consequences. The above, together with the after-effects, remains the focal point and main goal of the paper. Such a described systemic perspective may be used, for example, in environmental education. It can support a depiction or explanation of mechanisms and phenomena occurring within the forest system. In addition, it may be the basis for working out some ‘system instruments’ subsequently used in shaping attitudes and actions towards the forest and translating into the man– forest relationship. This can be reflected in decision-making process, broadly understood, preceding the actions taken in the field of forest system management.